Advances in the identification of novel cell signatures in benign prostatic hyperplasia and prostate cancer using single-cell RNA sequencing - Pan, Yu; Song, Qingqing; Lai, Bingjie; Ma, He (Frontiers in Immunology, 2026)
Nowadays, chronic benign and malignant prostatic diseases are prevalent, costly, and impose a significant burden. Benign prostatic hyperplasia (BPH), a common condition in the aging population, often coexists with localized prostate cancer (PCa). These diseases likely share underlying molecular mechanisms, which remain poorly understood. The exploration of novel cell subpopulations and specific biomarkers for accurate diagnosis and treatment of prostatic diseases is ongoing and holds great clinical promise. Prostate cell proliferation and immune inflammation are key contributors to the progression of BPH and PCa, involving various prostate and immune cell subpopulations. This raises important questions about how specific cell types drive phenotypic heterogeneity. Advanced single-cell RNA sequencing (scRNA-seq), a cutting-edge technology, offers unparalleled insights at the single-cell level. Similar to a microscope that identifies cell types within tissue samples, scRNA-seq elucidates cellular heterogeneity and diversity within single cell populations, positioning itself as a future-leading sequencing technology. Considering that BPH and PCa share androgen-dependent growth, chronic inflammation and specific microenvironmental changes, this review discusses recent discoveries of novel cell subpopulations and molecular signatures in BPH and PCa that can be dissected by scRNA-seq. It aims to help researchers better understand the molecular pathogenesis of these conditions while offering new therapeutic possibilities for clinical management of benign and malignant prostatic disorders.